Excessive plasmin compromises hepatic sinusoidal vascular integrity after acetaminophen overdose - Gao, Siqi (Hepatology, 2018)
The serine protease plasmin degrades extracellular matrix (ECM) components both directly and indirectly through activation of matrix metalloproteinases. Excessive plasmin activity and subsequent ECM degradation causes hepatic sinusoidal fragility and hemorrhage in developing embryos. We report here that excessive plasmin activity in a murine acetaminophen (APAP) overdose model likewise compromises hepatic sinusoidal vascular integrity in adult animals. We found that hepatic plasmin activity is upregulated significantly at 6 hr after APAP overdose. This plasmin upregulation precedes both degradation of the ECM component fibronectin around liver vasculature and bleeding from centrilobular sinusoids. Importantly, administration of the pharmacological plasmin inhibitor tranexamic acid or genetic reduction of plasminogen, the circulating zymogen of plasmin, ameliorates APAP-induced hepatic fibronectin degradation and sinusoidal bleeding. Conclusion: These studies demonstrate that reduction of plasmin stabilizes hepatic sinusoidal vascular integrity after APAP overdose.